Cloud computing utilization and mitigation of informational and marketing barriers of the SMEs from the emerging markets: Evidence from Iran and Turkey. (June 2019) - Hosseini, Sahab; Fallon, Grahame; Weerakkody, Vishanth; Sivarajah, Uthayasankar
Highlights: The study contributes theoretically to both EM-SMEs and international business literature. The study develops a new classification of the internationalization barriers that EM-SMEs face. The study proposes a series of cloud computing solutions for mitigating the barriers, resulting in the creation and testing of anew model. The empirical findings confirm that CCU can help EM-SMEs to mitigate a series of informational and marketing barriers. The key practical contributions offer insights to both EM-SMEs and CSPs that CCU is effective in mitigating the internationalization barriers. Abstract: This study seeks to investigate the effectiveness of Cloud Computing Utilization (CCU) in the mitigation of informational and marketing barriers for SMEs from the Emerging Market-Countries (EM-SMEs). A quantitative-research methodology was applied to collect data by using self-administered questionnaires from top managers of 227 SMEs based in Iran and Turkey. The study contributes theoretically to both small business and international business literature by developing a new classification of the internationalization barriers that EM-SMEs face, and proposing a series of cloud computing (CC) solutions for mitigating these barriers, resulting in the creation and testing of a new model. The empirical findings confirm that CCU can help EM-SMEs to mitigate a series of informational and marketing barriers. The key practical contributions of the study offer insights to both EM-SMEs and Cloud-Service-Providers (CSPs) on the extent to which CCU is effective in mitigating the internationalization barriers faced by EM-SMEs.